2D to 3D Manipulation and Assembly of Microstructures Using Optothermally Generated Surface Bubble Microrobots. Issue 45 (20th September 2019) - Dai, Liguo; Ge, Zhixing; Jiao, Niandong; Liu, Lianqing
Abstract: Hydrogel microstructures that encapsulate cells can be assembled into tissues and have broad applications in biology and medicine. However, 3D posture control for a single arbitrary microstructure remains a challenge. A novel 3D manipulation and assembly technique based on optothermally generated bubble robots is proposed. The generation, rate of growth, and motion of a microbubble robot can be controlled by modulating the power of a laser focused on the interface between the substrate and a fluid. In addition to 2D operations, bubble robots are able to perform 3D manipulations. The 3D properties of hydrogel microstructures are adjusted arbitrarily, and convex and concave structures with different heights are designed. Furthermore, annular micromodules are assembled into 3D constructs, including tubular and concentric constructs. A variety of hydrogel microstructures of different sizes and shapes are operated and assembled in both 2D and 3D conformations by bubble robots. The manipulation and assembly methods are simple, rapid, versatile, and can be used for fabricating tissue constructs. Abstract : Hydrogel microstructures are manipulated and assembled in 3D using laser and localized heating‐induced bubble microrobots. The conditions for generating and methods of controlling the size of bubbles are studied. Additionally, the mechanism of microstructural 3D flipping is studied. Microstructures of different shapes and sizes can be assembled into more complex constructs.